Linking soil microbial community structure to potential carbon mineralization: A continental scale assessment of reduced tillage. (May 2022) - Rieke, Elizabeth L.; Cappellazzi, Shannon B.; Cope, Michael; Liptzin, Daniel; Mac Bean, G.; Greub, Kelsey L.H.; Norris, Charlotte E.; Tracy, Paul W.; Aberle, Ezra; Ashworth, Amanda; Bañuelos Tavarez, Oscar; Bary, Andy I.; et al.
Abstract: Potential carbon mineralization (Cmin) is a commonly used indicator of soil health, with greater Cmin values interpreted as healthier soil. While Cmin values are typically greater in agricultural soils managed with minimal physical disturbance, the mechanisms driving the increases remain poorly understood. This study assessed bacterial and archaeal community structure and potential microbial drivers of Cmin in soils maintained under various degrees of physical disturbance. Potential carbon mineralization, 16S rRNA sequences, and soil characterization data were collected as part of the North American Project to Evaluate Soil Health Measurements (NAPESHM). Results showed that type of cropping system, intensity of physical disturbance, and soil pH influenced microbial sensitivity to physical disturbance. Furthermore, 28% of amplicon sequence variants (ASVs), which were important in modeling Cmin, were enriched under soils managed with minimal physical disturbance. Sequences identified as enriched under minimal disturbance and important for modeling Cmin, were linked to organisms which could produce extracellular polymeric substances and contained metabolic strategies suited for tolerating environmental stressors. Understanding how physical disturbance shapes microbial communities across climates and inherent soil properties and drives changes in Cmin provides the context necessary to evaluate management impacts on standardized measures of soil microbial activity. Highlights: Tillage impacts on soil microbial communities were assessed across North America. Reducing tillage selects for bacteria equipped to handle environmental stressors. Soil pH influences soil microbial resilience to physical disturbances. Taxa enhanced under minimum tillage inform potential carbon mineralization models. Intensive tillage in non-wheat rotations consistently altered the soil microbiome.